2023
DOI: 10.3389/fmicb.2023.1227309
|View full text |Cite
|
Sign up to set email alerts
|

Successful secukinumab therapy in plaque psoriasis is associated with altered gut microbiota and related functional changes

Xueshan Du,
Cong Yan,
Shuzhen Kong
et al.

Abstract: IntroductionThe role of gut microbiome dysbiosis in the pathogenesis of psoriasis has gained increasing attention in recent years. Secukinumab, targeting interleukin (IL)-17, has a promising efficacy in psoriasis treatment. However, it remains unclear the gut microbiota alteration and related functional changes caused by successful secukinumab therapy in psoriatic patients.MethodsIn our study, we compared the fecal microbiome profile between psoriatic patients after secukinumab successful treatment (AT) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…possibly attributed to the anti-inflammatory effects of the medication, which may have altered the gut microenvironment and improve microbial diversity. 14 It is worth noting that commonly used therapies, such as NSAIDs, methotrexate, leflunomide, and glucocorticoids, can inhibit the growth of specific gut bacteria, leading to gut microbiota diversity decrease. 15,16 The composition of the gut microbiota in AS patients after secukinumab therapy became more similar to that of the HC group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…possibly attributed to the anti-inflammatory effects of the medication, which may have altered the gut microenvironment and improve microbial diversity. 14 It is worth noting that commonly used therapies, such as NSAIDs, methotrexate, leflunomide, and glucocorticoids, can inhibit the growth of specific gut bacteria, leading to gut microbiota diversity decrease. 15,16 The composition of the gut microbiota in AS patients after secukinumab therapy became more similar to that of the HC group.…”
Section: Discussionmentioning
confidence: 99%
“…2 A link has been confirmed between the severity of subclinical intestinal inflammation and involvement of the sacroiliac joints. 14,17 Moreover, with the administration of secukinumab, these inflammatory changes in the gut may improve further, thereby reducing the risk of developing gastrointestinal symptoms. Since none of the patients in this group had IBD or gastrointestinal symptoms before or after treatment, we are not sure about the impact of secukinumab treatment on the incidence of IBD in AS patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, another study showed that treatment with secukinumab resulted in a more stable gut microbiome homeostasis, with an increase in the abundance of thickwalled bacterial phyla and a decrease in anaplastic bacterial phyla in patients receiving secukinumab. 161 These conflicting results highlight the complexity of the gut microbiota and individual differences among patients, making it challenging to understand the mechanisms behind these paradoxical effects fully. In conclusion, the impact of biologics on gut flora in psoriasis patients is an intriguing area of research.…”
Section: Il-23/il-17 and Psoriasismentioning
confidence: 99%
“…Gut microbiota, comprising trillions of microorganisms, significantly influences systemic immunity and inflammation ( Giambra et al, 2023 ; Li et al, 2023 ). Dysbiosis, an imbalance in the gut microbial composition, has been implicated in exacerbating psoriasis ( Buhas et al, 2022 ; Cai et al, 2023 ; Du et al, 2023 ). Alterations in gut microbiota can lead to increased intestinal permeability, allowing bacterial products to enter the circulation and potentially trigger systemic inflammation, which can exacerbate skin lesions.…”
Section: Introductionmentioning
confidence: 99%